The syntamorphological dynamics of the Galwa Bantu language in Gabon and rudiments for a bilingual dictionary - (:unkn) unknown (My University, 2007)
aThis thesis studies a bantu language of Gabon, Central Africa, the galwa (B. 11 c) which is a part of the B.10 language family. This African language belongs to the bantu group of the Benoué-Congo nib family which is itself a part of the Niger-Congo language grouping. This report first establishes the phonological base system and briefly introduces the morphophonology of the language. The syntaxmorphology characteristics of the language are covered as well as the processes of word formation (derivation and composition) and various grammatical categories and their place in the structure of noun and verb phrasing. Finally, this thesis covers the complexity of language wording and introduces a lexical model.
Keywords: African Research